ASUHAN KEBIDANAN IBU HAMIL TRIMESTER III DENGAN KETIDAKNYAMANAN PADA NY.N DI KLINIK BERSALIN SUNDARI KOTA CILEGON TAHUN 2019 - Umalihayati (Journal Of Applied Health Research And Development, 2020)
Low back pain in pregnancy is a musculoskeletal disorder that occurs in the lumbar region caused by the imbalance of the abdominal muscles and the erector spine akibar muscles of the fetus in the greater uterus so that the mother tries to divide the body weight and pull back at the shoulder. This attitude will add to the lordosis of the lower waist. The purpose of this case study is to provide obstetric care to pregnant women with discomfort in the third trimester This case research method is a qualitative case study because it is done by interview, and direct observation and register books and MCH books Midwifery care for pregnant women N with discomfort in the third trimester given treatment of Fe 1 x 1 tablet and calcium 1 x 1. It is recommended for all pregnant women to carry out routine pregnancy checks and pregnancy exercises and eat nutritiously balanced foods